2021
DOI: 10.1002/eng2.12446
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for system‐wide power system frequency model validation via measurement data

Abstract: Models are commonly used for various power system studies. This article presents a new framework to estimate and validate the parameters of the turbine-governor and also the load model in a multi-machine power system environment. The proposed method utilizes the center of inertia frequency and generating unit signals (especially active power) recorded by measurement devices to validate the parameters. The objective function is to minimize the total squared error between the simulated and the measured responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Owners of production stations are the vendors. The objective function of the problem of MGs participation in the capacity market is obtained as (1). 𝐷𝑅 is maintenance of distributed generation resources while the cost of responding to loads in dollars per kilowatt-day, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owners of production stations are the vendors. The objective function of the problem of MGs participation in the capacity market is obtained as (1). 𝐷𝑅 is maintenance of distributed generation resources while the cost of responding to loads in dollars per kilowatt-day, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Environmental considerations such as pollutions, greenhouse gases and landfills are the major issues in recent years [1]- [3] which has attracted a lot of attention for efficiency improvement of power systems and electrical machines [4], [5]. Development of the transmission system is a significant factor in power network design that determine the optimal configuration for a system based on load demand and increases network reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Validation of power system models is usually conducted as either System-Wide Simulations (SWS) or Hybrid Simulations (HS), see e.g. reference [9] and [10] respectively. These two methods have been compared by den Boer [11].…”
Section: Introductionmentioning
confidence: 99%
“…This is done by using a multi-model adaptive Kalman filtering, singular spectrum analysis and initialising the event playback after the first fast transients, which cannot be captured by the PMU. The particle swarm optimisation algorithm (PSO), is also commonly used to identify parameters, but a previous study [9] proposes a modified version of PSO to improve the results. This study also states that parameters can be identified using different events.…”
Section: Introductionmentioning
confidence: 99%
“…According to vehicle technologies office (VTO) of the United States (U.S.) department of energy, improving vehicle efficiency in U.S. is essential to reducing consumers' fuel costs, supporting domestic industry, minimizing pollution, and increasing energy security through low-cost, secure, and clean energy technologies [1]. The relationship between energy and fuel efficiency, environmental pollution and focus on the clean energy is driving the transportation to develop electric vehicle (EV) industry [2], [3].…”
Section: Introductionmentioning
confidence: 99%